Hush-hushing the Whole Matter: The UNHCR, Australia, and West Papuan Refugees - Neumann, Klaus (Refuge: Canada’s Journal on Refugees, 2006)
Between 1962 and 1973, thousands of refugees crossed from the Indonesian-controlled western half of the island of New Guinea into the Australian-controlled eastern half. The United Nations High Commissioner for Refugees (UNHCR) refrained from becoming involved in the issue, and from publicly criticizing the Australian government over its response to West Papuan asylum seekers. In return, the Australian government committed itself to keeping the High Commissioner informed about developments in New Guinea on the understanding that it would provide information on a strictly confidential basis. The article explores the High Commissioner’s possible motives for effectively condoning Australia’s refugee policies in Papua and New Guinea. It demonstrates the relevance of this historical case study for our understanding of current Australian policies and for evaluating the relationship between the UNHCR and governments.